Incidence and Grading of Complications After Gastrectomy for Cancer Using the GASTRODATA Registry: A European Retrospective Observational Study. Issue 5 (November 2020) - Baiocchi, Gian Luca; Giacopuzzi, Simone; Reim, Daniel; Piessen, Guillaume; Costa, Paulo Matos da; Reynolds, John V.; Meyer, Hans-Joachim; Morgagni, Paolo; Gockel, Ines; Santos, Lucio Lara; Jensen, Lone Susanne; Murphy, Thomas; et al.
Abstract : Objective: Utilizing a standardized dataset based on a newly developed list of 27 univocally defined complications, this study analyzed data to assess the incidence and grading of complications and evaluate outcomes associated with gastrectomy for cancer in Europe. Summary Background Data: The absence of a standardized system for recording gastrectomy-associated complications makes it difficult to compare results from different hospitals and countries. Methods: Using a secure online platform (www.gastrodata.org ), referral centers for gastric cancer in 11 European countries belonging to the Gastrectomy Complications Consensus Group recorded clinical, oncological, and surgical data, and outcome measures at hospital discharge and at 30 and 90 days postoperatively. This retrospective observational study included all consecutive resections over a 2-year period. Results: A total of 1349 gastrectomies performed between January 2017 and December 2018 were entered into the database. Neoadjuvant chemotherapy was administered to 577 patients (42.8%). Total (46.1%) and subtotal (46.4%) gastrectomy were the predominant resections. D2 or D2+ lymphadenectomy was performed in almost 80% of operations. The overall complications' incidence was 29.8%; 402 patients developed 625 complications, with the most frequent being nonsurgical infections (23%), anastomotic leak (9.8%), other postoperative abnormal fluid from drainage and/or abdominal collections (9.3%), pleural effusion (8.3%), postoperative bleeding (5.6%), and other major complications requiring invasive treatment (5.6%). The median Clavien-Dindo score and Comprehensive Complications Index were IIIa and 26.2, respectively. In-hospital, 30-day, and 90-day mortality were 3.2%, 3.6%, and 4.5%, respectively. Conclusions: The use of a standardized platform to collect European data on perioperative complications revealed that gastrectomy for gastric cancer is still associated with heavy morbidity and mortality. Actions are needed to limit the incidence of, and to effectively treat, the most frequent and most lethal complications. Abstract : Supplemental Digital Content is available in the text